Multimedia Development of English Learning for Recount Text Materials - Wijayanto, Mochlis Eko (International Journal of English Education and Linguistics (IJoEEL), 2019)
In this study aims to: (1) produce English learning multimedia products for recount text material, (2) find out the feasibility of English learning multimedia products for recount text material, and (3) find out the effectiveness of English learning multimedia multimedia products for recount text material for class VIII students at SMPNJ. This research method is a research and development (R&D) taken from the Alessi and Trollip model which consists of three stages, namely: (1) planning, (2) design, and (3) development. Data collection through observation, interviews, questionnaire sheets, and tests. Then, the data obtained were analyzed descriptively quantitatively. The effectiveness of the product was analyzed using the N-gain formula (normalized learning outcomes). The results of the study are as follows. (1) the products produced are multimedia in the form of English learning CDs for recount text material consisting of instructions, Competency Standards and Basic Competencies (SK and KD), description of material, summary, quiz, and evaluation; (2) the product developed is suitable for use as a complementary medium for learning English for recount text learning; (3) an increase in the average score of all students from the pretest and posttest results of 0.90 (N-gain â‰¥ 0.7). This means that the effectiveness of the product being developed is in the high category